Pendampingan Penyampaian SPT pada Toko Permata dan Kerajinan di Pasar Inpres Kebun Sayur Kota Balikpapan - Rinaldi, Muhammad; Ramadhani, Melda Aulia; Sudirman, Sitti Rahma; Ramadhani, Muhammad Harits Zidni Khatib; Yusuf, Abdurrahman Maulana (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This community service aims to provide understanding to the community in an effort to increase tax awareness. The target of this service is residents at the Balikpapan City Vegetable Garden Inpres Market. The solution that can be done is to be able to provide socialization to be able to understand what taxes are, especially in terms of submitting tax returns. This is done so that people in the Balikpapan City Vegetable Garden Inpres Market area become one of the taxpayers who obey their taxes. The result of this service is the socialization of materials that are in accordance with the problems of the community in the area, including Understanding of NPWP, Obligation to submit SPT, Submission of SPT online, Procedures for filling out SPT for WP OP, and Proof of SPT submission in the form of BPE. In addition to socialization, the distribution of flyers is also well realized.